(untitled) (Baghdad Science Journal, 2015)
Cadmium has been known to be harmful to human healthy , manily Via contaminated drinking water , food supplies , tobacco and industrial pollutant . The aim of this study was to determine the toxicity of new Cadmium (II) complex ( Bis[ 5- ( P- nitrophenyl ) – ? 4 – Phenyl- 1,2,4- triazole -3- dithiocarbamatohydrazide] cadmium (II) Hydra ( 0.5) and compare it with anticancer drug cyclophosphamide ( CP) in female albino mice . This complex causes to several alterations in Enzymatic activity of Glutamate Pyruvate Transaminase (GPT) and Alkaline Phosphatase (ALP ) in three organs after the treatment of mice with different doses of a new cadmium (II) complex ( 0.09 / 0.25ml , 0.18/ 0.5ml and 0.25mg /0.7 ml /30 gm of mouse ) for three days by the decreased of Glutamate Pyruvate Transaminase activity in lung , Liver and kidney , while the Alkaline Phosphatase activity was increased in kidney , lung and liver . The results were indicated that no significant differences ( P > 0.05 ) in Glutamate Pyruvate Transaminase activity between the treatment of mice with cadmium ( II ) complex and cyclophosphamide (CP) in the liver , kidney and Alkaline Phosphatase activity in the liver at each three doses .